Seeking an intersectional "convergence des luttes" in the occupied theaters of Marseille. (1st September 2022) - Ingram, Mark
Abstract : In recent culture wars in France, critics claim that intersectionality "fractures everything" (Emmanuel Macron, Le Point ). Stéphane Beaud and Gérard Noiriel argue that "identitarian" discourses—and an emphasis on race in particular—have contributed to divisions in popular classes and divided progressive activists ( Le Monde Diplomatique ). At issue in these debates is whether explicit references to modes of gendered and racialized oppression will be recognized as legitimately universalist in accordance with the French republican tradition, a question explicitly addressed by recent scholarship proposing a rethinking of universalism—more "concrete" for Lépinard and Mazouz (2021) and more "inclusive" for Hourya Bentouhami (2020) . This article examines the occupation of two theaters in Marseille as a setting where universalist ideals about citizenship were expressed and put into practice. In March 2021, more than 100 theaters were occupied across France, some by the CGT (Confédération Générale du Travail) union, and some by theater students. Whereas unions prioritized economic issues in the arts sector, students framed the occupations as a broader struggle against racism, sexism, police violence, and environmental degradation, arguing that these must be considered together. Drawing on interviews and occupation documents, this article examines the differences and points of alignment between students and unions. This analysis highlights points of collaboration and exchange, and also shows how the intersectional priorities of students extended the scope of the occupations to include other marginalized populations. Here, an intersectional approach fostered collaboration not only across two currents of social justice activism, but also with other partners across the urban territory of Marseille, thereby showing intersectionality's value and compatibility within contemporary French social justice activism.